Seizures, Psychosis, and Cerebral Vascular Malformation: A Rare Chain of Events - Ismail Hanine; Khadija Benallel; Roukaya Benjelloun; Mohamed Kadiri (Case Reports in Psychiatry)
Background. In psychiatry, anatomical abnormalities are sometimes forgotten, and this can mislead doctors into thinking that the diagnosis is purely psychiatric. A physical examination is important whenever it is possible. Even though cerebral arteriovenous malformations (cAVMs) are rare and can go unnoticed, in some cases they can cause clinical symptoms, which is a complication. Case Presentation. In this case, we describe a patient with no prior medical or psychiatric history having a cAVM diagnosed after showing psychotic symptoms (delusion and disorganized thoughts and behavior). The deep 4 × 5 cm cAVM was discovered after admitting the patient to psychiatric ward, the neurological cause has been considered after a recorded seizure, which brings the following question: Is the clinical presentation a direct result of the cAVM or is it postictal? Conclusions. An abnormality leading to another, here is how we could describe our patient’s psychopathology leading to psychotic symptoms. The two hypotheses explaining this case report have a low rate of occurring making this a rare case. Either way, neurological cause cannot be overlooked even if the clinical presentation is typical.